Measurement of health outcomes - Montarat Thavorncharoensap (2018)
Health outcomes are one of the most important components of health technology assessments (HTAs). All HTA outcomes should be measured from a relevant sample using a properly designed study and method. A number of recommendations on health outcome measurements are made in this second edition of Thailand's HTA guidelines. In particular, the use of final outcomes, rather than surrogate outcomes, in HTAs is stressed. Where surrogate outcomes are used, strong justification and evidence must be provided. Effectiveness is preferred over efficacy. The relative treatment effect (the difference between health outcome that would be experienced by patients receiving the technology and that experienced by the same group were they to receive an alternative technology) should be derived from a systematic review of head-to-head RCTs. Mixed treatment comparison (MTC) should be used only to provide supplementary data that cannot be obtained from a head-to-head comparison. Where no direct comparison evidence exists, indirect comparison and observational study data can be used.